P483 Infliximab but not adalimumab drug levels predict faecal calprotectin response in Inflammatory Bowel Disease patients on dose-intensified anti-TNF therapy. (27th May 2021) - Noack, S; Little, R; Vaz, K; Ward, M; Sparrow, M
Abstract: Background: Secondary loss of response (SLOR) to infliximab (IFX) and adalimumab (ADA) is common and dose intensification is effective in a proportion of patients. Drug level targets associated with response as measured by faecal calprotectin (FCP) after anti-TNF intensification have not been well established. Methods: Retrospective observational study of consecutive adult patients with Crohn's disease (CD) or ulcerative colitis (UC) with SLOR commenced on dose-intensified IFX (5mg/kg 6 weekly) or ADA (40mg weekly) between May 2013-August 2020. Patients were managed via a protocolised virtual clinic. Trough anti-TNF drug levels and FCP were measured at baseline, and at 6 and 12 months post dose intensification. FCP response was defined as ≤150μg/g. Inter-group and longitudinal comparisons used Mann-Whitney U and Wilcoxon signed-rank tests, respectively. ROC curves evaluated anti-TNF drug levels predictive of FCP response. Results: Of 78 patients (56% male, median age 40 years), 60 had CD (58% on IFX) and 18 had UC (100% on IFX). There were no significant differences in patient or disease demographics between FCP responders and non-responders at 6 or 12 months. At 6 months, median IFX level and increment in level from baseline were higher in FCP responders than non-responders in both CD and UC (Table 1). At 6 months, achieving an IFX level ≥5.7μg/mL in CD (AUC 0.82, sensitivity 88%, specificity 65%, p=0.012; Figure 1A) and an IFX level ≥5.2μg/mL in UC (AUC 0.89, sensitivity 100%, specificity 73%, p=0.015; Figure 1B) best predicted FCP response. ADA levels at 6 months and both IFX and ADA levels at 12 months were not predictive of FCP response in any cohort. Conclusion: After dose-intensified IFX, CD and UC patients achieving FCP response had greater absolute and increment in drug levels than those with elevated FCP. IFX levels ≥5.7μg/mL and ≥5.2μg/mL at 6 months are predictive of FCP response in CD and UC, respectively. ADA levels were not predictive of FCP response.